2014
DOI: 10.1038/nature13290
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic electromagnetic noise disrupts magnetic compass orientation in a migratory bird

Abstract: Electromagnetic noise is emitted everywhere humans use electronic devices. For decades, it has been hotly debated whether man-made electric and magnetic fields affect biological processes, including human health. So far, no putative effect of anthropogenic electromagnetic noise at intensities below the guidelines adopted by the World Health Organization has withstood the test of independent replication under truly blinded experimental conditions. No effect has therefore been widely accepted as scientifically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
309
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(353 citation statements)
references
References 31 publications
(18 reference statements)
19
309
1
1
Order By: Relevance
“…However, very recent experiments (51), designed to replicate the earlier study (50), under much more stringently controlled conditions, failed to find specific effects at the Larmor frequency. In contrast, very weak broadband fields were found to disrupt the birds' magnetic compass orientation capabilities (51,52 Spin Relaxation and Magnetic Disorientation. The third major condition for the emergence of the spike is that the spin coherence times of the radicals should be longer than 1 μs, which in turn means that the librations of the radicals within their binding pockets must be of relatively low amplitude and not too sluggish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very recent experiments (51), designed to replicate the earlier study (50), under much more stringently controlled conditions, failed to find specific effects at the Larmor frequency. In contrast, very weak broadband fields were found to disrupt the birds' magnetic compass orientation capabilities (51,52 Spin Relaxation and Magnetic Disorientation. The third major condition for the emergence of the spike is that the spin coherence times of the radicals should be longer than 1 μs, which in turn means that the librations of the radicals within their binding pockets must be of relatively low amplitude and not too sluggish.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach would be to extend the behavioral experiments mentioned above in which broadband subnanotesla electromagnetic noise was found to prevent European robins from using their magnetic compass (52). If, for example, the birds' ability to orient was disrupted by 1-to 100-kHz but by not 1-to 10-kHz broadband noise, this would provide evidence for radical pair lifetimes and spin relaxation times in the range of 10−100 μs (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the emerging picture suggests that magnetic cues are an essential feature of animal spatial perception and behaviour, with a functionality going well beyond 'classical' navigational tasks ( Cervený et al, 2011;Dommer et al, 2008;Kimchi et al, 2004;Philips et al, 2010). Recently it has been shown that anthropogenic pollution in terms of electromagnetic background noise in and near cities are sufficient to disrupt such a magnetic sensor (Engels et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a truly fascinating analogy can be made with the quantumbiological compass that is believed to enable organisms such as migratory birds to sense the Earth's magnetic field [38,39].…”
Section: Magnetic Field Effects In Organic Semiconductorsmentioning
confidence: 99%